Свято-Михайлівська церква в селі Собич - Кириєвський, В.Д. (Сіверщина в історії України, 2021)
Стаття присвячена найстарішій в Шосткинському району Свято-Михайлівській церкві в с. Собич. За переказами селян, збереженими місцевим краєзнавцем Миколою Степановичем Жирним (1940–2014), церква була в селі ще в дотатарські часи. У статті наведені нові, раніше невідомі архівні дані 1910 р. про церкву та прицерковні будівлі. The article is dedicated to the oldest St. Michael’s Church in the village of Sobych in Shostka district. According to the legends of the peasants, preserved by the local ethnographer Mykola Stepanovych Zhyrnyi (1940–2014), the church was in the village in the pre-Tatar years. The article presents new previously unknown archival data of 1910 about the church and church buildings. There have been three churches in the village of Sobych in Prydesnia throughout its history. The first of them burned in a large fire that swept over the village in a hurricane. Traces of the fire are found by diggers of new burial pits at a depth of 1.5 meters of new burial pits dug at the edge of the old cemetery on the right bank of the river Dovhi Vody. On March 31, 1671, Archimandrite of the Novhorod-Siversk Spaso-Preobopazhensky Monastery Mykhailo Lezhaisky granted Ivan Holodenko a siege letter on the right to drive and settle people on the monastery lands in the Usobych tract. Since then, the second St. Michael’s Church in its history has appeared in Sobych. It was small in size. The church stood for almost a century and was dismantled, and in its place a new large wooden church was built on a brick foundation. In 1929, the Bolsheviks closed the Sobych church in 1932, Komsomol members tore off its crosses and dropped all six bells from the bell tower. A granary was set up in the church. In 1939 the warehouse was rebuilt as a village club. During the war in 1943, the church housed a military hospital. After the war, the club started working in the church again. In 1968, the club was renovated and renamed the “House of Culture” of the collective farm “Red Ukraine”. Young people had fun in the beautiful church every night until it caught fire on the night of December 26- 27, 1976 from a short circuit in the wiring.